Pentingnya integrasi nilai-nilai dakwah rasulullah di madinah untuk membentuk generasi pelajar yang berakhlakul karimah - Sholihah, Nailatus (Maliki Interdisciplinary Journal, 2025)
This study emphasizes the necessity of integrating the values of Prophet Muhammad’s da’wah in Medina into modern educational frameworks to shape morally upright Islamic students. By examining the Prophet’s teachings in Medina such as justice, social cohesion, and ethical governance this research highlights their relevance in developing students’ moral character in higher education. The study also explores practical strategies for incorporating these values into academic curricula, aiming to nurture individuals who embody Islamic virtues and contribute positively to society. The author uses a library study method that comes from books and journals that have been previously researched, so that its truth can be accounted for. This approach serves as a foundational step in strengthening moral education for a new generation of students.